Evaluation of Forage Berseem (Trifolium alexandrinum L.) for Yield and Nutritive Qualities Under Varying Seed Rates and Phosphorus Fertilization - Arif, Mohd.; Pourouchottamane, R.; Arvind Kumar; D.L. Gupta; Ravindra Kumar (Indian Journal of Animal Nutrition, 2022)
A field experiment was conducted at agriculture farm, ICAR-Central Institute for Research on Goats, Makhdoom, Mathura (Uttar Pradesh) during the rabi season of 2020-21 to study the effect of different seed rates and levels of phosphorus fertilizer on dry matter yield and nutritive value in berseem. The treatments consist of three seed rates viz. 20 kg ha-1, 25 kg ha-1 and 30 kg ha-1 and five levels of phosphorus viz. 40 kg P2O5 ha-1, 60 kg P2O5 ha-1, 80 kg P2O5 ha-1, 100 kg P2O5 ha-1 and 120 kg P2O5 ha-1. The experiment was laid out in factorial randomized block design with three replications. The result showed that maximum total dry matter yield (8.65 t ha-1); crude protein yield (1501.2 kg ha-1) and ether extract yield (317.7 kg ha-1) was recorded with the seed rate of 30 kg ha-1 which was at par with the seed rate of 25 kg ha-1. However, proximate chemical constitute and other quality parameters viz. TDN content, dry matter intake, digestible dry matter, relative feed value and quality; and net energy for lactation did not influenced significantly due to different seed rates in berseem. Further it was revealed that application of 120 kg P2O5 ha-1 recorded highest value of crude protein (19.20, 18.15, 17.12 and 17.05%), TDN content (62.46, 61.62, 60.49 and 59.66 %), dry matter intake (2.71, 2.68, 2.51 and 2.49 %), relative feed quality (137.46, 134.16, 123.80 and 120.90 %) and net energy for lactation (1.51, 1.49, 1.47 and 1.45 Mcal kg-1) in I, II, III and IV cut, respectively. However, application of 100 and 120 kg P2O5 ha-1 recorded at par value of all these quality parameters.